Not changes in membrane fluidity but proteotoxic stress triggers heat shock protein expression in Chlamydomonas reinhardtii. (27th September 2017) - Rütgers, Mark; Muranaka, Ligia Segatto; Schulz‐Raffelt, Miriam; Thoms, Sylvia; Schurig, Juliane; Willmund, Felix; Schroda, Michael
Abstract: A conserved reaction of all organisms exposed to heat stress is an increased expression of heat shock proteins (HSPs). Several studies have proposed that HSP expression in heat‐stressed plant cells is triggered by an increased fluidity of the plasma membrane. Among the main lines of evidence in support of this model are as follows: (a) the degree of membrane lipid saturation was higher in cells grown at elevated temperatures and correlated with a lower amplitude of HSP expression upon a temperature upshift, (b) membrane fluidizers induce HSP expression at physiological temperatures, and (c) membrane rigidifier dimethylsulfoxide dampens heat‐induced HSP expression. Here, we tested whether this holds also for Chlamydomonas reinhardtii . We show that heat‐induced HSP expression in cells grown at elevated temperatures was reduced because they already contained elevated levels of cytosolic HSP70A/90A that apparently act as negative regulators of heat shock factor 1. We find that membrane rigidifier dimethylsulfoxide impaired translation under heat stress conditions and that membrane fluidizer benzyl alcohol not only induced HSP expression but also caused protein aggregation. These findings support the classical model for the cytosolic unfolded protein response, according to which HSP expression is induced by the accumulation of unfolded proteins. Hence, the membrane fluidity model should be reconsidered. Abstract : In the past decades, many articles have been published promoting the idea that the expression of heat shock proteins (HSPs) in land plants is regulated by changes in the fluidity of the plasma membrane. However, even more work on non‐plant organisms indicates that HSP expression is triggered by the accumulation of unfolded proteins. Using Chlamydomonas as a model organism, we show here that all lines of evidence in support of a role of membrane fluidity in controlling HSP expression can be explained by the classical model for the unfolded protein response. We therefore challenge the membrane fluidity model.